الـقراءات القرآنية وأثرها في حفظ المقاصد البيئية والجمالية - Zayd Thabit Abdulrahman; Mohd Faizulamri Mohd Saad; Sabri Mohamad (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study aims to analyze the miraculous purposes of Quranic readings in terms of the environmental and beautiful objectives and to employ these readings to extract the creative and renewable meanings which come in the context of each type of Quranic reading and Quranic words. The problem statement of this study lies in the following question” To what extent do the Quranic readings highlight the values that indicate maintaining the environment as well as producing their role in highlighting the beautiful touches that take into account the psychological style in maintaining the decoration in the environment, and how to take into consideration the meanings of creativity, whether in art, beautification, and adornment. The study utilized the analytical and descriptive approach based on collecting scientific material to investigate, conclude and analyze the significance of the Quranic readings. The findings revealed that the Quranic readings referred to the preservation of environmental objectives and made preserving and sustaining them a human necessity and a legal obligation, especially since Allah Almighty prepared the reasons that enabled creatures and beings to work on the earth and strive to cultivate it. Quranic readings highlighted in their styles the use of the psychological method in dealing with the environment by talking about its elements. They showed aesthetic objectives when they showed creative meanings, such as carving mountains, building roofs, and raising girls on jewelry and adornment. The findings also revealed that the Quranic readings considered what extends to the Hereafter.